Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/hgv.2017.60
|View full text |Cite
|
Sign up to set email alerts
|

Novel and recurrent RNF213 variants in Japanese pediatric patients with moyamoya disease

Abstract: Moyamoya disease is a progressive steno-occlusive condition of the main intracranial arteries that results in the compensatory formation of fragile moyamoya vessels at the base of the brain. RNF213 is the most significant susceptibility gene and is often found with the p.Arg4810Lys founder variant in East Asian patients. We identified three putatively deleterious variants of this gene from three pediatric patients: two were novel, and one was a recurrent missense variant previously reported in other pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 20 publications
(24 reference statements)
0
14
1
8
Order By: Relevance
“…The PubMed database was searched for English publications reporting RNF213 variants detected in MMD patients up to December 2018. We selected studies which performed comprehensive retrieval of RNF213 variants in MMD patients, and found 14 matched studies that reported RNF213 variants detected in MMD patients 18,19,[26][27][28][29][30][31][32][36][37][38][39][40] . One study investigated only exons 41-68 considered to be the genomic hypervariable region of RNF213 31 , whereas the other studies comprehensively investigated the entire RNF213 gene.…”
Section: Review Of Previously Reported Rnf213 Variants Detected In MMmentioning
confidence: 99%
“…The PubMed database was searched for English publications reporting RNF213 variants detected in MMD patients up to December 2018. We selected studies which performed comprehensive retrieval of RNF213 variants in MMD patients, and found 14 matched studies that reported RNF213 variants detected in MMD patients 18,19,[26][27][28][29][30][31][32][36][37][38][39][40] . One study investigated only exons 41-68 considered to be the genomic hypervariable region of RNF213 31 , whereas the other studies comprehensively investigated the entire RNF213 gene.…”
Section: Review Of Previously Reported Rnf213 Variants Detected In MMmentioning
confidence: 99%
“…Without understanding the pathogenetic mechanisms, our data from case-control design could not access the causal relationship between RNF213 variants and ICASO. Furthermore, ICASO and MMD, both RNF213-related disorders, are progressive cerebrovascular diseases [35,44]. Because our study lacked follow-up data, we did not provide information about the progression of ICASO or the prognostic value of RNF213 variants.…”
Section: Discussionmentioning
confidence: 99%
“…Moyamoya disease (MMD) is a peculiar disease, characterized by progressive steno-occlusion of the distal ends of bilateral internal carotid arteries (ICAs) and their proal vascular network at the base of the brain (moyamoya vessels) is formed as a result of progressive ischemic changes in the brain [1], [2], [3]. The high incidence of MMD in Japanese population and high proportion of familial cases suggest the involvement of a genetic factor, particularly polymorphism in RNF213 gene [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%